Experimental investigation on hybrid fibre reinforced polymer epoxy LY556 composites by vacuum bag molding. (2022) - Karthik, K.; Ramesh, V.; Kolappan, S.; Arunkumar, K.; Udayaprakash, J.; Rameshkumar, R.
Abstract: Hybrid fiber reinforced polymer composite materials had significant properties more strength light weigh. In current research is to recognize the different stacking sequences were used. Two different fibers were namely carbon and kenaf with epox Ly556 matrix. The originality of this work is combined the natural and synthetic fibre to vaccum bag molding methods, to fabricated sandwich is used 5-layers with four sample stacking sequence are prepared. The developed Samples are cued and it has been performed various mechanical properties test. The C/C/K/C/C sacking sequences are produced 170 MPa tensile strength when compared other samples. The neat carbon fibres are have better properties, but when compared cost and environmental effect normally synthetic fibre are produced some effect.